'Uncertain destinies' student recruitment and retention on GNVQ intermediate programmes - Huddleston, P (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This paper discusses the rationale for conducting research into the issue of learning to write in the workplace. The paper argues that although managers in a wide range of workplaces acknowledge the important role that writing plays in their activities, there is little evidence of systematic support in helping new workers to learn how to write in ways that are appropriate to the needs and requirements of specific organisations. It is argued that we need to learn more about the kind of higher level literacy knowledge that might enable people to transfer and adapt foundation literacy knowledge to new settings, and also about the role of formal education in initiating such higher level knowledge.